2007
DOI: 10.2166/wst.2007.284
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of some characteristics of aerobic granules and sludge flocs from sequencing batch reactors

Abstract: Physical, chemical and biological characteristics were investigated for aerobic granules and sludge flocs from three laboratory-scale sequencing batch reactors (SBRs). One reactor was operated as normal SBR (N-SBR) and two reactors were operated as granular SBRs (G-SBR1 and G-SBR2). G-SBR1 was inoculated with activated sludge and G-SBR2 with granules from the municipal wastewater plant in Garching (Germany). The following major parameters and functions were measured and compared between the three reactors: mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…The reactors were fed with the acetate-containing synthetic wastewater. The proper trace element solution was added [ 16 ]. Influent COD Cr was 800–1000 mg/L and NH 4 + -N was 55–60 mg/L.…”
Section: Methodsmentioning
confidence: 99%
“…The reactors were fed with the acetate-containing synthetic wastewater. The proper trace element solution was added [ 16 ]. Influent COD Cr was 800–1000 mg/L and NH 4 + -N was 55–60 mg/L.…”
Section: Methodsmentioning
confidence: 99%
“…Restated, strong shear force would not only "compact" aggregates into granules, but also would provide sufficient oxygen to suppress filament growth for a long-term operational stability. Keeping the operation at an appropriate solids retentions time (SRT), or the so-called sludge age, was essential to maintain granule stability (Li et al, 2007a). Li et al (2007b) investigated aerobic granulation in membrane bioreactor, and measured the total extracellular polymeric substances (EPS) contents on day 5 as 39.6 mg gSS − 1 , and as 749.5 mg gSS − 1 on day 28.…”
Section: Sbr Operationmentioning
confidence: 99%
“…The use of quantitative image analysis techniques for monitoring wastewater treatment processes has been initiated by Sezgin et al (1978), who found a well-defined relationship between the sludge volume index (SVI) and the filament quantity in activated sludge. Recently, Li et al (2007) compared several characteristics of activated sludge flocs and granules by using different techniques including image analysis. The statistical tool principal component analysis (PCA) was used to relate image analysis information with the sludge settleability in terms of SVI (Jenné et al, 2006).…”
Section: Introductionmentioning
confidence: 99%